A Designed α‐GalCer Analog Promotes Considerable Th1 Cytokine Response by Activating the CD1d‐iNKT Axis and CD11b‐Positive Monocytes/Macrophages. Issue 14 (8th June 2020) - Ma, Juan; He, Peng; Zhao, Chuanfang; Ren, Quanzhong; Dong, Zheng; Qiu, Jiahuang; Jing, Yang; Liu, Sijin; Du, Yuguo
Abstract: Selective helper T cell 1 (Th1) priming agonists are a promising area of investigation for immunotherapeutic treatment of various diseases. α ‐galactosylceramide ( α ‐GalCer, KRN7000), a well‐studied Th1‐polarizer, simultaneously induces helper T cell 2 (Th2)‐type responses, which is a major drawback for its clinical applications. Based on surflex‐docking computation, α ‐GalCer‐diol, with added hydroxyl groups in the acyl chain, is designed and synthesized. Structural analyses reveal stronger affinity between α ‐GalCer‐diol and cluster of differentiation 1d (CD1d), leading to enhanced antigen presentation by dendritic cells (DCs) and self‐activation, as reflected by tight binding of the T‐cell receptor (TCR)/KRN7000/CD1d ternary complex and elevated production of interleukin 12 (IL‐12) and interferon‐ γ (IFN‐ γ ). Consequently, invariant natural killer T cells (iNKTs) are activated and exhibit an improved Th1‐type cytokine profile ex vivo and in vivo. Different from KRN7000, α ‐GalCer‐diol markedly boosts the expansion of the CD11b + subpopulation and enhances IFN‐ γ content in CD11b + cells. These reinforced Th1‐type responses collectively endow α ‐GalCer‐diol more robust antitumor activity in a xenograft animal model using B16‐F10 melanoma cells. Together, the data demonstrate a new mechanism through which α ‐GalCer‐diol induces stronger Th1‐type responses by stimulating CD11b + leukocyte expansion and DC‐conducted CD1d‐restricted and TCR‐mediated iNKT activation. Hence, this study may facilitate the development of novel Th1 priming agonists. Abstract : Designed α ‐galactosylceramide ( α ‐GalCer)‐diol generates higher affinity with cluster of differentiation 1d (CD1d) by forming hydrogen bonds with polar residues in A' pocket of CD1d, leading to stronger helper T cell 1 (Th1)‐type responses and antitumor activity through a novel mechanism of stimulating CD11b + leukocyte expansion and Th1‐priming state. This study may facilitate the development of new Th1 priming agonists.